The role of motor nerve conduction: in cervical radiculopathy patients - Garg, Meenakshi; Gupta, Saurabh; Sood, Sushma; Singh, Mohita (International Journal of Research in Medical Sciences, 2019)
Background: Cervical radiculopathy is the clinical description of when a nerve root in the cervical spine becomes inflamed or damaged, resulting in a change in neurological function. Neurological deficits, such as numbness, altered reflexes, or weakness, may radiate from the neck into the shoulder, arm, hand, or fingers. Patient also complains of tingling, numbness or loss of sensation along with the nerve root dermatome. It is a substantial cause of disability and morbidity, and its cost-effective evaluation and treatment are crucial so there is a definite need to establish a cost effective, reliable, and accurate means for establishing the diagnosis of cervical radiculopathy. Electrodiagnostic tests are the closest to fulfil these criteria out of which nerve conduction tests are one of the electrodiagnostic test. Methods: In this study motor nerve conduction of ulnar and median nerve done in 30 clinically proven cervical radiculopathy patients Results: There are significant decrease in the conduction velocity of both nerve (median nerve (51.60±7.5), Ulnar nerve (50.60±5.6)) and significantly increased in the mean latency of both nerve (median nerve (6.02±2.4), ulnar nerve (5.8±1.8)). Conclusions: Authors concluded that MNC is the specific test for the diagnosis of cervical radiculopathy. At least the MNC of both nerves included in diagnostic criteria of cervical radiculopathy.